2009
DOI: 10.1007/s00535-008-2304-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hepatoma-derived growth factor in the growth inhibition of hepatocellular carcinoma cells by vitamin K2

Abstract: These findings suggested that regulation of the HDGF gene expression is one of the crucial mechanisms of vitamin K(2)-induced cell growth suppression for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
(52 reference statements)
0
31
0
Order By: Relevance
“…In various malignant cancers, HDGF expression is highly elevated and has been demonstrated to be a pleiotropic growth factor with motogenic, mitogenic, and angiogenic properties. This may be mediated by an abnormal cell cycle regulation, antiapoptosis pathway, and alternative extracellular matrix activity [18][19][20]. However, little is known about how this upregulation occurs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In various malignant cancers, HDGF expression is highly elevated and has been demonstrated to be a pleiotropic growth factor with motogenic, mitogenic, and angiogenic properties. This may be mediated by an abnormal cell cycle regulation, antiapoptosis pathway, and alternative extracellular matrix activity [18][19][20]. However, little is known about how this upregulation occurs.…”
Section: Discussionmentioning
confidence: 94%
“…HDGF participates in many cellular processes including endothelial angiogenesis [15], cardiovascular differentiation [16], and renal and liver development [17]. Although HDGF is expressed ubiquitously in normal tissue and cell lines, including HuH-7, COS-7, aortic vascular smooth muscle cells, endothelial cells, fibroblasts, and fetal hepatocytes, its expression is dramatically increased in fetal tissues and cancers [18][19][20]. It has been shown that HDGF increases the tumorigenic potential and mitogenic and angiogenic activity of a variety of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…For promoter activity assay, cells were cotransfected with 1 mg HDGF-driven luciferase vector (32) or E-cadherin-driven luciferase vector (generous gift from Dr. Yu-Sun Chang, Chang Gen University, Taipei, Taiwan; ref. 33) and the 0.2 mg Renilla reniformis luciferase reporter vector (Promega).…”
Section: Transfection and Luciferase Measurementmentioning
confidence: 99%
“…Yamamoto et al suggested that regulation of the expression of the hepatoma-derived growth factor gene is one of the crucial mechanisms of MK-4-induced cell growth suppression in HCC. Hepatomaderived growth factor stimulates the proliferation of HCC cells after its translocation to the nucleus by use of bipartite nuclear localization signals [16]. Azuma et al [17] suggested that activation of steroid and xenobiotic receptors (SXR) by MK-4 contributes to the tumor suppressive effects on HCC cells.…”
Section: Mechanisms Of Growth Inhibition Of Hcc Cells By Mk-4mentioning
confidence: 99%